The Influence of Peer Health Education Toward the Decreasing Risk of Heart Disease - Riza Fikriana; Al Afik (Universitas Airlangga, 2018)
Introduction: Heart disease is the number one cause of death in Indonesia. Promotional efforts through the provision of health education and counselling through Peer Health Education is one of the primary prevention strategies that can be undertaken to prevent the occurrence of heart disease. The purpose of this study is to prove the influence of Peer Health Education in reducing the risk of heart disease.Methods: The research method used in this study was quasi-experimental with a pre-test-post-test non-equivalent control group design. The samples were taken from 56 people using the purposive sampling technique. The first group of 28 people was the experimental group and the second group of 28 people was the control group. Before and after treatment, both groups were measured concerning their knowledge, lifestyle behaviour, blood pressure, blood glucose levels, blood cholesterol levels and risk assessment of heart disease. Data analysis was done by using the Friedman Test with a 95% significance level.Results: The results showed that Peer Health Education was able to improve the respondents' knowledge about having a healthy lifestyle, changing the behaviour of the respondents, i.e. behaviour of consuming sweet foods, controlling blood pressure and decreasing the risk of heart disease.Conclusion: Based on the result, health promotion efforts through a Peer Health Educator can continue to be done as one method to improve heart health in the community. Thus, the expectation of morbidity and mortality due to heart disease can be lowered.